BORRELIOSIS: A HIDDEN THREAT FOR KAZAKHSTAN - Bissenbay, A.O.; Zhigailov, A.V.; Maltseva, E.R.; Egemberdieva, R.A.; Skiba, Y.A.; Mamadaliyev, S.M. (Eurasian Journal of Applied Biotechnology, 2019)
Tick-borne borreliosis, commonly known as Lyme disease or Lyme borreliosis, is a natural focal zoonotic transmissive disease caused by the Borreliella burgdorferi sensu lato complex. If left untreated, the disease can cause damage to the nervous system, joints, or skin, as well as lead to development of chronic atrophic diseases. Diagnosis of borreliosis remains a challenge owing to variations in clinical symptoms and manifestations, simultaneous damage to several organs, and frequent latent persistence of the pathogen in the body, leading to misdiagnosis or late diagnosis. This situation results in defects or delays in the provision of medical care with a high frequency of residual consequences, resulting in temporary disability for the patient that imposes a significant social-economic burden. Ticks of the genus Ixodes are the main carrier of the disease, which inhabit the mountain regions of eastern and southeastern Kazakhstan. However, the distribution area of these ticks has been expanding in recent years owing to the effects of climate change, resulting in an increase of natural foci of tick-borne borreliosis. We here provide updated data on the epidemiology, etiology, pathogenesis, and diagnostic methods for Lyme borreliosis, along with an overview of modern molecular methods for the analysis of borrelia. Moreover, we offer an overall assessment of the risks associated with this disease for Kazakhstan.